NAGARI LAKITAN DARI DESA KE NAGARI TAHUN 2001-2010 - Elvida, Oriza - (Pendidikan Sejarah, 2014)
This Thesis examines about tow the polemic changes in the government system in Nagari Lakitan. In this thesis will look at tow the development of Nagari Lakitan after returning to the Nagari system government based to economic and social culture development community Nagari Lakitan.this paperalms to how the systems government in the Nagari Lakitan and then how development Nagari Lkitan after return into Nagari administration system of government Nagari Lakitan progress. This research includes the study of history therefore research on Nagari Lakitan from village to Nagari 2001-2010 history methode with steps likes: 1. Heuristic, the collection of data from primary data through interview with thw actors and secondary sources from books relevan bodes anf anything to do with this paper (literature study), 2. Source critic, 3. Analysis synthesis and interprestation,4. Historiography that write history data so that itbecomes a scientific paper. From the discussion done can be see that, the Nagari Lakitan is village in the coastal district subdistrict Lengayang, south pesisi. With issuance of law no 22 1999, the local government of west Sumatra restore the system to the village government administration system to village or better known as back to Nagari. Back to the some system of government as government village trustee who headed village and assited by traditional leaders village wich has been handed down since the former to return to the village government system makes Nagari LAakitan move flexibillityin promoting their area. With the return to the village in Lakitan system of government the impact of the case on the progress of economic educational and social culture society Nagari Lakitan.